Detection of tetraploidization in chromophobe renal cell carcinoma: Insights and pitfalls. Issue 12 (6th August 2020) - Di Mauro, Ilaria; Ambrosetti, Damien; Vignot, Louis; Roussel, Jean‐François; Dadone‐Montaudie, Bérengère; Peyron, Annie‐Claude; Quintens, Hervé; Durand, Matthieu; Amiel, Jean; Pedeutour, Florence
Abstract: Chromosomal losses resulting in a marked hypodiploidy are a specificity of chromophobe renal cell carcinoma (ChRCC), the third most frequent type of kidney cancer. Its detection is useful in challenging cases. However some ChRCC, especially the eosinophilic variant, do not exhibit hypodiploidy and deserve to be better explored. Using comparative genomic hybridization (array‐CGH) we observed chromosomal gains in five cases of nonmetastatic ChRCC. Our objective was to determine whether these apparent chromosomal gains were instead losses within a near‐polyploid genome. We performed a retrospective and prospective molecular study of 26 cases of ChRCC retrieved among 643 renal tumors (2012‐2019). All tumors were analyzed using array‐CGH (Agilent) and array‐CGH (Affymetrix) coupled to single nucleotide polymorphism analysis (array‐SNP). In silico manual centralization of the fluorescence ratio, fluorescence in situ hybridization (FISH) and next generation sequencing were made in the five cases suspected of polyploidy. Tetraploidization was observed in 19% of our series of ChRCC. None of the methods used individually could identify both chromosomal losses and tetraploidy. Only the combination of manual recentring of array‐CGH and FISH provided relevant results. B‐allele frequency results indicated that tetraploidization occurred secondarily to chromosomal losses in four cases while it preceded losses in one case. Tetraploidization is a frequent but underestimated phenomenon in ChRCC that may be overlooked using the individual standard genomic methods. Its potential clinical consequences are not identified yet. Whether the mechanisms that induce chromosomal losses in ChRCC are the same that generate tetraploidization is not known.